Clinical evaluation of allogeneic mesenchymal stem cells for Alzheimer's disease: Human/Human trials: Inflammation. (7th December 2020) - Oliva, Anthony A.; Baumel, Bernard; Brody, Mark; Agronin, Marc; Herskowitz, Brad; Bookheimer, Susan Y; McClain‐Moss, Lisa; Hitchinson, Ben; Ramdas, Kevin; Pena, Andrea; Diaz, Liliana A.; Green, Geoff; et al.
Abstract: Background: Therapeutic interventions that can broadly target the complex multiple pathological features of Alzheimer's disease (AD) would be highly desirable approaches for treating these disorders. Mesenchymal stem cells (MSCs) have pleiotropic mechanisms of action that make them highly attractive as therapeutic candidates for AD. These include powerful anti‐inflammatory properties, ability to improve vascular functioning, ability to promote intrinsic regenerative mechanisms, and ability to promote beta‐amyloid clearance. Given these highly desirable properties of MSCs, we set out to clinically evaluate their safety and therapeutic potential for AD, using a proprietary formulation called Longeveron Mesenchymal Stem Cells (LMSCs). Method: Central to this study is a Phase I clinical trial powered to evaluate the safety of LMSCs for mild AD. Provisional efficacy is also being evaluated. This trial is double‐blinded, randomized, and placebo‐controlled, and registered with ClinicalTrials.gov (NCT02600130). Trial oversight includes FDA, an IRB, and an independent Data Monitoring Safety Board (DSMB). Subjects are enrolled after passing a 3‐step screening process, which sequentially consists of clinical diagnosis of mild AD, a confirmatory MRI, and a confirmatory PET scan using a beta‐amyloid tracer. Enrolled subjects are randomized to receive a single intravenous infusion of a low‐dose of LMSCs (20 million cells), a high‐dose of LMSCs (100 million cells), or placebo. Evaluated for safety and effect are performed over the 1‐year follow‐up. Result: This multi‐site trial has proceeded ahead of schedule, and was fully enrolled as of September 2019. The trial was designed to enroll 30 patients; ultimately, 33 patients were enrolled. Results support the high safety profile LMSCs for AD: the DSMB has found no safety concerns, and the primary objective of no treatment‐related serious adverse events (SAEs) within 1 month post‐treatment was met. Preliminary data suggest the feasibility of biomarker analyses for evaluating effect changes, and the final lock and unblinding is anticipated in late 2020. Conclusion: The results support the conclusion that LMSCs are safe in AD patients, and that advancing to higher phase clinical studies is warranted. We thank the Alzheimer's Association for supporting this research through the Part the Cloud Challenge on Neuroinflammation grant awards #PTC C‐16‐422443 and PTC‐CS‐19‐623225.